Climate and phylogenetic history structure morphological and architectural trait variation among fine‐root orders. Issue 6 (14th August 2020) - McCormack, M. Luke; Kaproth, Matthew A.; Cavender‐Bares, Jeannine; Carlson, Eva; Hipp, Andrew L.; Han, Ying; Kennedy, Peter G.
Summary: Fine roots mediate below‐ground resource acquisition, yet understanding of how fine‐root functional traits vary along environmental gradients, within branching orders and across phylogenetic scales remains limited. Morphological and architectural fine‐root traits were measured on individual root orders of 20 oak species (genus Quercus ) from divergent climates of origin that were harvested after three growing seasons in a glasshouse. These were then compared with similar measurements obtained from a phylogenetically diverse dataset of woody species from the Fine‐Root Ecology Database (FRED). For the oaks, only precipitation seasonality and growing season moisture availability were correlated to aspects of root diameter and branching. Strong correlations among root diameters and architecture of different branch orders were common, while correlations between diameter and length were weakly negative. By contrast, the FRED dataset showed strong positive correlations between diameter and length and fewer correlations between root diameter and architectural traits. Our findings suggest that seasonal patterns of water availability are more important drivers of root adaptation in oaks than annual averages in precipitation and temperature. Furthermore, contrasting patterns of trait relationships between the oak and FRED datasets suggest that branching patterns are differentially constrained at narrow vs broad phylogenetic scales.